Konsepsi Hak Cipta Ditinjau dari Distribusi Kekayaan Menurut Teori Hukum Ekonomi Syariah: Conception Of Copyright Is Reviewed From The Distribution Of Wealth According To The Theory Of Islamic Economic Law - Fazal Akmal Musyarri (CV Rewang Rencang, 2022)
Intellectual Property Rights (IPR) is a right that arises from the results of human brain thinking that produces a product or process that is useful for human life. The object of IPR arrangement is a work that arises or is born from human intellectual ability. IPR itself has many kinds such as copyright, brand rights, patents, industrial design, trade secrets, protection of plant varieties, to the design of integrated circuit layouts. IPR itself in the context of Islamic Law is included as a gift of Allah S.W.T.. In this paper, the author is interested in studying IPR in the view from the point of view of property ownership theory and its implications. This is considering the utilization of IPR that can bring commercial value to IPR holders as an exclusive right. Whether the conception is in accordance with Islamic sharia or there are other concepts that are more ideal to be applied.